The potential of Makerere University heritage (1922-2011) resources for urban tourism development - Okiror, Pau. (Kampala, 2013)
Unpublished thesis (Msc. ENR) - Makerere University, 2013.
Includes bibliographical references.
Keywords: Tourism -- Government policy -- Uganda; Touris industry -- Makerere University -- Uganda